Unexpected Phenotype of Mice Lacking Shcbp1, a Protein Induced during T Cell Proliferation - Buckley, Monica W.; Arandjelovic, Sanja; Trampont, Paul C.; Kim, Taeg S.; Braciale, Thomas J.; Ravichandran, Kodi S. (PLOS ONE, 2014)
T cell development and activation are highly regulated processes, and their proper execution is important for a competent immune system. Shc SH2-domain binding protein-1 (Shcbp1) is an evolutionarily conserved protein that binds to the adaptor protein ShcA. Studies in Drosophila and in cell lines have strongly linked Shcbp1 to cell proliferation, embryonic development, growth factor signaling, and tumorigenesis. Here we show that Shcbp1 expression is strikingly upregulated during the β-selection checkpoint in thymocytes, and that its expression tightly correlates with proliferative stages of T cell development. To evaluate the role for Shcbp1 during thymic selection and T cell function in vivo, we generated mice with global and conditional deletion of Shcbp1. Surprisingly, the loss of Shcbp1 expression did not have an obvious effect during T cell development. However, in a mouse model of experimental autoimmune encephalomyelitis (EAE), which depends on CD4+ T cell function and mimics multiple features of the human disease multiple sclerosis, Shcbp1 deficient mice had reduced disease severity and improved survival, and this effect was T cell intrinsic. These data suggest that despite the striking upregulation of Shcbp1 during T cell proliferation, loss of Shcbp1 does not directly affect T cell development, but regulates CD4+ T cell effector function in vivo.